Considerations for the Prophylactic Extraction of Asymptomatic Unerupted Third Molars (International Journal of Medical and Surgical Sciences, 2014)
The extraction of asymptomatic unerupted third molars (TMNE) is called as "prophylactic" since it try to anticipate the appearance of recognized pathological conditions that ranged from simple dental crowdings to the development of cysts and tumors. This supposed predictability and the implicit risks of this surgery have resulted in arguments that defend, question or accept under certain limits this procedure with still unresolved dilemmas. Nevertheless the clinical activity seems to be much less judicious, with reports that continue promoting the indiscriminate extraction of TMNE with total lack of symptoms or pathological processes. Since the prophylactic extraction of asymptomatic TMNE is a recurrent topic of discussion for its relevance according to the different clinical odontologic disciplines, which many of them enclose its own perspectives only to clinics or to biology, a review on different considerations of this practice is presented, the risks and benefits are discussed, and some ethical dilemmas are exposed to the promotion of a dentallex artis.
Keywords: Third molar; Prophylactic extraction; Risk and benefits